2017
DOI: 10.1111/anae.14115
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative outcomes following cardiac surgery in non‐anaemic iron‐replete and iron‐deficient patients – an exploratory study

Abstract: Iron deficiency anaemia is strongly associated with poor outcomes after cardiac surgery. However, pre-operative non-anaemic iron deficiency (a probable anaemia precursor) has not been comprehensively examined in patients undergoing cardiac surgery, despite biological plausibility and evidence from other patient populations of negative effect on outcome. This exploratory retrospective cohort study aimed to compare an iron-deficient group of patients undergoing cardiac surgery with an iron-replete group. Consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 22 publications
2
32
2
1
Order By: Relevance
“…In observational studies of patients undergoing abdominal or cardiac surgery, pre‐operative non‐anaemic iron deficiency was associated with poor outcomes, including: increased rates of postoperative infection; transfusion; fatigue; and prolonged hospital stay . Although it is presently unknown whether pre‐operative correction of non‐anaemic iron deficiency may offset the excess of risk of postoperative complications, some guidelines recommend peri‐operative iron supplementation for patients with non‐anaemic iron deficiency .…”
Section: Should We Treat Iron Deficiency Without Anaemia?mentioning
confidence: 99%
“…In observational studies of patients undergoing abdominal or cardiac surgery, pre‐operative non‐anaemic iron deficiency was associated with poor outcomes, including: increased rates of postoperative infection; transfusion; fatigue; and prolonged hospital stay . Although it is presently unknown whether pre‐operative correction of non‐anaemic iron deficiency may offset the excess of risk of postoperative complications, some guidelines recommend peri‐operative iron supplementation for patients with non‐anaemic iron deficiency .…”
Section: Should We Treat Iron Deficiency Without Anaemia?mentioning
confidence: 99%
“…In 100 consecutive cardiac procedures, preoperative ID was frequent (37%), and it was associated with preoperative anemia, higher RBCT requirements, and postoperative fatigue [11]. In a retrospective cohort of 277 cardiac surgeries, prevalence of ID was 39%, and univariate analysis suggested that ID was associated with a longer hospital stay and fewer days alive out of hospital on postoperative day 90 [12]. In a retrospective cohort of 115 total hip arthroplasties at the first author’s center, patients with ID ( n = 54: 45 ID, 9 FID) have lower perioperative Hb, higher prevalence of preoperative anemia, higher RBCT rate, without differences in pretransfusion Hb, and a trend to longer hospital stays than those without ID [unpubl.…”
Section: Prevalence and Consequences Of Perioperative Anemiamentioning
confidence: 99%
“…Herein, the study findings added some credits to the compiled knowledge about the strong incidence of preoperative ID (31%) in elective cardiac surgery patients and the high prevalence of red blood cell transfusion (23% v 12%, p < 0.03) during intraoperative surgery in this population. 2,3 Although supported by the literature, 4 the authors did not find significant difference in the postoperative red blood cell transfusion despite a high incidence of combined surgical procedure in the ID group. This result could be explained partly by the small size of this study that analyzed 272 patients.…”
Section: Is Iron Deficiency Correction the Real Ultimate Goal Of Patimentioning
confidence: 74%